Effects of Aging on the Obstacle Negotiation Strategy while Stepping over Multiple Obstacles - Chien, Jung Hung; Post, Jerod; Siu, Ka-Chun (Scientific reports, 2018)
Forty-seven percent of falling accidents in older adults are caused by tripping over obstacles. Understanding what strategies are involved in obstacle negotiation in older adults could reduce fall risks. There is a paucity of research investigating how healthy adults negotiate multiple obstacles, which may better reflect the complexity of the real environment. The presence of a second obstacle has induced mixed results in the obstacle negotiation of healthy older adults with the interval between obstacles two steps apart. This study extended the knowledge to understand what strategies healthy younger and older adults used to step over two obstacles placed at three-step-length apart. Twenty healthy subjects performed 2 tasks: level ground walking and stepping over two obstacles. The height of each obstacle was set at 10% of subjects’ leg height. We found that aging significantly increased the toe clearance in leading and trailing legs when stepping over the obstacles at a three-step-length interval. Toe clearance was higher while stepping over the second obstacle than the first one in older adults. These results had two-fold meanings: the three-step-length interval was long enough to trigger the adjustment of the obstacle negotiation strategy, and aging led older adults to use conservative negotiation strategies.